Delegation and Cartel Stability - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1994)
The effect of delegation on cartel stability is addressed in a duopoly for a homogeneous product, under Cournot competition. The main findings are that if only one firm is managerial, the critical discount factor is increased by the presence of a weight attached to sales, so that cartel stability is decreased, while if both are managerial the opposite holds. As a consequence, the inclusion of sales in both firms' objective function represents an incentive towards collusion.
Keywords: 330